The Meaning of Accountability in Mosque Management: An Ethnomethodological Approach - Juardi, Muhammad Sapril Sardi; Alimuddin, Alimuddin; Said, Darwis; Binti Johari, Fuadah (LAA MAISYIR: Jurnal Ekonomi Islam, 2025)
This study aims to interpret accountability in mosque management at Tarbiyah Mosque in Pinrang Regency, Raya Pancarijang Mosque in Sidrap, and Al Istiqamah Mosque in Rumbia, Enrekang. Novelty this research employs a qualitative method using an ethnomethodology approach to examine the everyday practices of mosque management within the social, cultural, and religious contexts of each mosque community.  The results of the study indicate that the practice of publicly reading out donations before the congregation embodies social legitimacy and strengthens the congregation’s trust in the mosque administrators. Furthermore, the meaning of accountability within the mallele donation practice reflects the values of sincerity, trustworthiness, and reciprocal relations between the administrators and the congregants. Finally, the interpretation of accountability expressed through the use of weekly information boards illustrates the value of information openness and transparency.